Antibacterial activities of lactic acid bacteria isolated from rotten vegetables - Lee, Pei Zhen (2015)
Rising trend of foodborne illness and emergence of antimicrobial resistance in Malaysia pose serious threat to the public and thus a new and effective antibacterial agent is required to address the situation. The non-pathogenic lactic acid bacteria (LAB) with high antibacterial potential can be isolated from rotten vegetables and showed inhibitory activity toward foodborne pathogens. The objective of this study was to isolate and identify LAB, also to determine the inhibitory activity from rotten vegetables against foodborne pathogens. A total of eight LAB isolates were isolated from seven types of rotten vegetables. The antibacterial activities of isolates against Escherichia coli ATCC 8739, Staphylococcus aureus ATCC 6538, Listeria monocytogenes L10 were determined using the agar-well diffusion method. E. coli ATCC 8739 appeared to be the most susceptible test organisms to LAB isolates as the inhibition zone of all LAB isolates against E. coli ATCC 8739 were obviously larger than the other test organisms. The antibacterial agents were stable within limit range of pH values from pH 2.0 to 5.0. Antibacterial activity was not observed when the pH of the supernatant was adjusted to above pH 6.0. Inhibitory activity of isolates can be observed even at high temperature from 50oC to 100oC, yet the zone of inhibition showed a decrease trend in all isolates as the temperature goes up.